Annatto Tocotrienol Improves Indices of Bone Static Histomorphometry in Osteoporosis Due to Testosterone Deficiency in Rats - Chin, Kok-Yong (Nutrients, 2014)
This study aimed to evaluate the effects of annatto tocotrienol on indices of bone static histomorphometry in orchidectomized rats. Forty male rats were randomized into baseline (BL), sham (SH), orchidectomized (ORX), annatto tocotrienol-treated (AnTT) and testosterone enanthate-treated (TE) groups. The BL group was sacrificed upon receipt. All rats except the SH group underwent bilateral orchidectomy. Annatto tocotrienol at 60 mg/kg body weight was administered orally daily to the AnTT group for eight weeks. Testosterone enanthate at 7 mg/kg body weight was administered intramuscularly once weekly for eight weeks to the TE group. The rat femurs were collected for static histomorphometric analysis upon necropsy. The results indicated that the ORX group had significantly higher osteoclast surface and eroded surface, and significantly lower osteoblast surface, osteoid surface and osteoid volume compared to the SH group (p < 0.05). Annatto tocotrienol and testosterone enanthate intervention prevented all these changes (p < 0.05). The efficacy of annatto tocotrienol was on par with testosterone enanthate. In conclusion, annatto tocotrienol at 60 mg/kg can prevent the imbalance in bone remodeling caused by increased osteoclast and bone resorption, and decreased osteoblast and bone formation. This serves as a basis for the application of annatto tocotrienol in hypogonadal men as an antiosteoporotic agent.